Multimode vibronic spectra of the Holstein molecular crystal model - Liu, Qingmei (2011)
Vibronic spectra of the Holstein model for molecular crystals are investigated using the dynamical mean field theory with the additional aid of the multi-mode Brownian oscillator model. The effects of temperature, intermolecular transfer integral, damping constant and quadratic coupling on the vibronic spectra are examined, and spectra in the presence of two phonon modes are studied in detail. Results from the dynamical mean field theory are corroborated by those from the multi-mode Brownian oscillator model. Strength and weakness of the two approaches are discussed to point out the corresponding regimes of application for each.